PROBLEMS OF TAX RISK MANAGEMENT IN THE CONDITIONS OF THE COVID-19 PANDEMIC - SHEVCHUK, Anton (Scientific journal «World of Finance», 2021)
Introduction. The theoretical bases of tax risks are considered and the author’s approach to interpretation of their essence is offered. The directions of the COVID-19 pandemic’s impact on tax revenues to the State Budget of Ukraine have been studied and the factors of intensification of tax risks have been determined. On this basis, scientifically sound recommendations for improving the management of tax risks in Ukraine in the economic crisis. The purpose of the article is to study the areas of intensification of tax risks in the context of the COVID-19 pandemic and the development of scientifically sound proposals for improving the management of tax risks in the face of new challenges for fiscal authorities. Results. The main directions of the impact of the COVID-19 pandemic on tax revenues to the State Budget of Ukraine are assessed. It is proved that the manifestations of the economic crisis are the main factors of intensification of tax risks in Ukraine, which are expressed in significant losses of budget revenues. Ways to optimize the mechanism of VAT refunds and directions of audit of tax benefits in order to minimize tax risks are proposed. The mechanisms of obligatory fiscalization of micro and small business settlements through the introduction of registrars of settlement operations on favorable terms for business owners without the need to hire additional employees are outlined. Possibilities of realization of the project of electronic customs as one of elements of creation of a positive business climate and minimization of tax risks are considered. Perspectives. Promising areas of research may be the study of psychological, administrative, technological, political factors of tax risks in Ukraine.